MO039IDENTIFICATION OF A RECURRENT SYNONYMOUS GENETIC VARIANT IN NPHP3 LEADING TO NEPHRONOPHTHISIS AND CONGENITAL HEPATIC FIBROSIS. (29th May 2021) - Olinger, Eric; Al Alawi, Intisar; Molinari, Elisa; Ali Faqeih, Eissa; Al Hamed, Mohamed; Barroso-Gil, Miguel; Wilson, Ian; Research Consortium, Genomics England; Sayer, John
Abstract: Background and Aims: Whole exome sequencing (WES) is becoming part of routine clinical and diagnostic practice and has been extensively applied in research studies as well as for diagnostic utility to detect various novel genes and variants. Filtering of variants and scoring variants in terms of pathogenicity still represents a major challenge and may explain why ∼50% of patients remain without diagnosis after initial assessment. Method: In this study, we performed WES to determine the genetic cause of a hepato-renal ciliopathy syndrome in a genetically unsolved consanguineous family from Oman with 2 affected children. For variants filtering and annotation Qiagen Clinical Insight tool was used. Database searches for identical alleles in patients with similar phenotypes were performed using Genomics England, UK Biobank and a Saudi Arabian cohort. RNA studies were used to confirm a splicing defect. This research was made possible through access to the data and findings generated by the 100, 000 Genomes Project and from UK Biobank, a major biomedical database. Results: Initial bioinformatic analysis of WES data from 2 affected sibs excluded obvious pathogenic variants in known genes associated with primary ciliopathy syndromes with liver and kidney phenotypes. However, by manual curation of variants in candidate genes, a rare homozygous synonymous allele in NPHP3 was identified (c.2805C>T; p.(Gly935Gly)), mid-exon 20 and within a region of shared homozygosity on chromosome 3. Correct segregation was confirmed via Sanger sequencing in the parents and the 2 affected sibs. The variant was rare in gnomAD (2/251374 alleles) and was found heterozygously in just one individual within the UK Biobank cohort of 200, 000 exomes. Using various in silico tools, the allele was shown to activate a cryptic splice donor site in the middle of exon 20. RT-PCR with sequencing of parental whole blood RNA confirmed alternative splicing leading to frameshift p.Gly935GlyfsTer47. The identical homozygous allele was identified in 2 additional unsolved families within the Genomics England 100, 000 Genomes Project and in 1 Saudi Arabian family with similar hepato-renal phenotypes. Conclusion: This study shows that automated filtering of WES data may exclude synonymous variants which are pathogenic, especially if they are mid-exon. Here we identified a recurrent synonymous NPHP3 variant leading to a splice defect as the cause of a hepato-renal ciliopathy phenotype in four families. In unsolved cases, rare synonymous alleles in candidate genes need to be reassessed for impact on RNA splicing and possible pathogenicity.